2019
DOI: 10.1016/j.wavemoti.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

On solutions of a Boussinesq-type equation with displacement-dependent nonlinearity: A soliton doublet

Abstract: In this paper the permanent profile waves governed by a Boussinesq-type wave equation are analysed. The model involves displacement-type nonlinearities and dispersion terms. Physically such a model equation describes longitudinal waves (density change) in biomembranes which have an internal structure composed by lipid molecules. The possible solutions are constructed and analysed. The phase plane analysis and numerical simulation reveal a novel phenomenon: the possible existence of a soliton doublet.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…( 14)) lead to the bounded solution and permit regulation of the width of the soliton needed to match the experimental results. In addition, it has been shown that depending on the coefficients, several types of solutions may exist, including trains of solitons, oscillatory solutions, and the soliton doublet [60,61]. It has also been demonstrated that as Eq.…”
Section: Remarks On Mathematics Needed For Modellingmentioning
confidence: 99%
“…( 14)) lead to the bounded solution and permit regulation of the width of the soliton needed to match the experimental results. In addition, it has been shown that depending on the coefficients, several types of solutions may exist, including trains of solitons, oscillatory solutions, and the soliton doublet [60,61]. It has also been demonstrated that as Eq.…”
Section: Remarks On Mathematics Needed For Modellingmentioning
confidence: 99%
“…The propagation of the AP is accompanied also by the dynamical deformation of the biomembrane. A mathematical model for the longitudinal deformation is proposed by Heimburg and Jackson [31] and later improved by Engelbrecht et al [18,20,52,53].…”
Section: Mathematical Models and Modellingmentioning
confidence: 99%
“…Two forced Boussinesq-type models are derived for a circular rod with axially symmetric loading and longitudinal pre-stretch from the full problem formulation using the presence of small parameters. Basic dynamical properties of the models are compared, and the equations are suggested as models for the related experimental research.Soliton solutions of a Boussinesq-type equation with displacement-type nonlinearities linked to the Heimburg-Jackson model describing longitudinal waves (density charge) in biomembranes are investigated in the paper by T. Peets et al [7]. The possibility of the existence of a soliton doublet, an ensemble of two co-existing…”
mentioning
confidence: 99%
“…Soliton solutions of a Boussinesq-type equation with displacement-type nonlinearities linked to the Heimburg-Jackson model describing longitudinal waves (density charge) in biomembranes are investigated in the paper by T. Peets et al [7]. The possibility of the existence of a soliton doublet, an ensemble of two co-existing…”
mentioning
confidence: 99%